Time management as a correlate of quality service delivery in private secondary schools in Rivers South-East Senatorial District, Rivers State - Pritta Menyechi Elenwo; Ruth Ejuwa Wike (S&Co Publishing, 2024)
The research investigated time management as a correlate of quality service delivery in private secondary schools in Rivers South-east Senatorial District, Rivers State. The research adopted a correlational research survey design. A sample of 400 made up of 25 administrators, 155 teaching, and 220 non-teaching staff respectively made up the study sample size. The sample size of 400 was determined using the Taro Yamane formula. The data collection instrument were structured questionnaires titled, Time Management Questionnaire and Quality Service Delivery Questionnaire. The instruments used for data collection were face and content authenticated by two experts from Measurement and Evaluation and one expert from the Department of Educational Management of the Faculty of Education at Rivers State University. The reliability coefficients of the instruments were 0.80 for the time management questionnaire and 0.78 for the quality service delivery questionnaire, which indicates a reasonable reliability coefficient. The research questions posed were answered using Pearson Product Moment Correlation Coefficient (PPMCC), while Z-ratio was used to test the formulated hypotheses. Conclusions drawn from the study exposed a significantly high positive relationship between time scheduling, priority setting, task delegation, and quality service delivery in private secondary schools. The researchers recommend that staff in private schools should meticulously schedule tasks and strictly adhere to them for optimal service delivery. Additionally, tasks should be prioritized to achieve organizational goals for quality service delivery. Furthermore, school administrators and staff should delegate tasks when faced with heavy workloads to enhance task flow and ensure quality service delivery.